Conformity Analysis of GTFS Routes and Bus Trajectories - Queiroz, Andreza Raquel M.; Santos, Veruska B.; Nascimento, Dimas C.; Pires, Carlos Eduardo S. (Anais do Simpósio Brasileiro de Banco de Dados (SBBD), 2019)
General Transit Feed Specification (GTFS) is a standard data format generated by transportation agencies of most of the cities worldwide to provide scheduled data of their services. Despite being the standard in the public transportation field, applications that consume GTFS data may face two problems: outdated versions, since some transportation agencies do not provide GTFS in the same frequency that transit changes; and discrepancy with positioning data sent by the buses. This paper provides a conformity analysis of GTFS routes and bus positioning data from multiple cities. We have found inconsistencies related to GPS route labels and GTFS routes. We also classify the conformity of bus trajectories and enumerate the main inconsistencies found in data analysis.